Associations of breastfeeding or formula feeding with infant anthropometry and body composition at 6 months - Muna J. Tahir; Keisuke Ejima; Peng Li; Ellen W. Demerath; David B. Allison; David A. Fields (Wiley, 2021)
Abstract The objective of this study was to investigate the associations of mode of feeding with infant anthropometric and body composition variables at 6 months of age. We studied 259 infants whose exclusive mode of feeding (breast or formula) to 1 month was confirmed. Standard anthropometric characteristics of the infants (weight, length and weight‐for‐length z scores) were obtained, and body composition (total fat mass, fat‐free mass, trunk fat mass and body fat percent) was measured using dual‐energy X‐ray absorptiometry (DXA) at 6 months (±12 days). General linear models were used to test the associations of mode of feeding with infant anthropometric and body composition variables at 6 months after adjustment for maternal and infant covariates. In this cohort of predominantly breastfed, White infants of highly educated mothers, fat‐free mass was lower (P = .002), and trunk fat mass (P = .032) and body fat percent (P < .001) were greater in breastfed infants than in formula‐fed infants at 6 months of age. After adjustment for covariates, total fat‐free mass was significantly lower (β = −372 g, [SE = 125, P = .003]), and body fat percent was significantly greater (β = 3.30, [SE = 0.91, P < .001]) in breastfed infants than in formula‐fed infants. No other significant associations were observed. These findings support those of previous studies reporting greater fat‐free mass in formula‐fed infants during the first 6 months of life. Additional research is warranted to explore whether differences in infant body composition by mode of feeding persist throughout the life course and to assess causality.